Oral cancer knowledge, attitudes, and practices among senior dental students in Yemen: a multi-institution study - Anas Shamala; Esam Halboub; Sadeq Ali Al-Maweri; Hesham Al-Sharani; Mona Al-Hadi; Raheq Ali; Hajer Laradhi; Heba Murshed; Marwan Mansoor Mohammed; Kamran Ali (BMC, 2023)
Abstract Background The "Knowledge, attitude, and practice (KAP)" approach is crucial in health system. Appreciating the current KAP status will reveal the extent of the efficiency of applied health strategies, and subsequently help to determine the appropriate health policy to be employed for improving the health indicators of a given disease/condition, including Oral Cancer (OC). This large-scale cross-sectional study aimed to assess knowledge, attitude, and practice on OC among senior dental students in Yemen. Methods A pre-validated online questionnaire was used for data collection. It consisted of a series of close-ended questions on knowledge, attitudes and practices related to OC. Yemeni dental students in clinical levels (4th and 5th years) from nine dental schools based in four major cities were invited to complete the survey. The SPSS Version 28.0 was used for data analysis. Differences by different grouping factors were assessed by Chi-squared and Mann Whitney-U tests, as appropriate. Results A total of 927 students completed the questionnaire: a response rate of 43%. While the majority identified smoking (93.8%), and smokeless tobacco (92.1%) as potential risk factors of OC, only 76.2% recognized sun exposure as a risk factor for lip cancer and only 50% were aware of old age as a risk factor of OC. Regarding clinical signs of OC, 84.1% reported that OC can present as non-healing ulcer, but only two thirds of the participants recognized that OC can present as a white and/or red lesion. With respect to practices, although 92.1% reported asking their patients regarding oral habits, only 78% reported they regularly carry out a soft tissue examination. Only 54.5% of the participants considered themselves to be well-trained to provide smoking cessation advice, and 21% were confident regarding their knowledge on OC. The 5th year students showed significantly better knowledge and practices than the 4th year students did (p < 0.01). Conclusion The study suggests significant gaps in knowledge, attitudes, and practices of senior dental students in Yemen regarding OC. The findings also underscore the urgent need to improve OC teaching and training of undergraduate dental students, and to provide periodic well-structured continuing professional development activities for dental professionals.